Solvent extraction of oil from Arachis Hypogaea seed – the effect of extraction time and type of solvent: article / Nur ‘Amirah Mohamed Sufian, Faiznur Mohd Fuad - Mohamed Sufian, Nur ‘Amirah; Mohd Fuad, Faiznur (2018)
Vegetable oils are being used extensively due to their wide application mainly in food industry and can be derived from various seeds, nuts and fruits. Arachis hypogaea or better known as peanut or groundnut is popular as reliable oil source with wide applications and potential. In this study, the extraction of oil from peanut will be performed by using solvent extraction technique. Optimization of parameters which are the extraction time (hr) and the type of solvents were investigated by using one-factor-at-a-time (OFAT) method. Meanwhile, the temperature, solid-to-liquid ratio and particle size were kept constant at 60℃, 1:6 and 710 um respectively. The optimum values obtained for extraction and type of solvent were found to be 4 hr and ethyl acetate respectively with oil recovery of 48.27%